The Role of Women in Kabbalistic Tradition: a Personal Note - Akke Mathilde M de-Jong (International Journal of Religious and Cultural Studies, 2023)
This article seeks to portray the role of women in Kabbalistic Tradition. Through many accounts both personal journey's note as well as literature study, it can be stated that women's positioning of roles are imprinted on what is considered “acceptable” behaviour. Religious structure, i.e. rules and regulations are needed to “force” people into desirable and preferred behaviour. This article also shed some views on the Tanakh and Talmud, the New Testament and the Ten Commandments, as well as the Quran relating to women's role.